2013
DOI: 10.1080/08974438.2013.723999
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship Between Perceived Quality Cues and Quality Attributes in the Purchase of Meat in Malaysia

Abstract: This study utilises the Total Food Quality Model to gain a better understanding of how Malaysian consumers make their decision to purchase fresh/chilled meat. We examine the association between quality cues and desired values (quality attributes) with regards to food that is guaranteed Halal, safe to eat, healthy and nutritious, has a good taste, represents good value for money, and is produced in a way which protects the environment and worker welfare. The findings reveal that different quality cues assume di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
(81 reference statements)
1
6
0
Order By: Relevance
“…The consumers' preferences and WTP for meat attributes have been an ongoing focus in many consumer studies (Grunert et al, 2004;Font-i-Furnols and Guerrero, 2014;Kehagia et al, 2007). Studies on meat quality attributes indicated several intrinsic (color, fat content and marbling) and extrinsic (price, origin and quality labels) cues as the most important factors in the consumers' intention to purchase food (Chamhuri and Batt, 2013;Font-i-Furnols and Guerrero, 2014;Grunert et al, 2004;Grunert, 2005;Henchion et al, 2014;Hoffmann, 2000;Kennedy et al, 2004;Verbeke and Viaene, 1999). Some studies examined these cues as quality attributes for poultry meat (Castellini et al, 2008;Fletcher, 2002;Samant and Seo, 2016;Verbeke and Viaene, 1999).…”
Section: Selection Of Poultry Meat Attributes and Consumers' Wtpmentioning
confidence: 99%
“…The consumers' preferences and WTP for meat attributes have been an ongoing focus in many consumer studies (Grunert et al, 2004;Font-i-Furnols and Guerrero, 2014;Kehagia et al, 2007). Studies on meat quality attributes indicated several intrinsic (color, fat content and marbling) and extrinsic (price, origin and quality labels) cues as the most important factors in the consumers' intention to purchase food (Chamhuri and Batt, 2013;Font-i-Furnols and Guerrero, 2014;Grunert et al, 2004;Grunert, 2005;Henchion et al, 2014;Hoffmann, 2000;Kennedy et al, 2004;Verbeke and Viaene, 1999). Some studies examined these cues as quality attributes for poultry meat (Castellini et al, 2008;Fletcher, 2002;Samant and Seo, 2016;Verbeke and Viaene, 1999).…”
Section: Selection Of Poultry Meat Attributes and Consumers' Wtpmentioning
confidence: 99%
“…The poor eating quality of meat is blamed for this drop (Apostolidis & McLeay, 2019; Bonny et al, 2018). However, consumer preferences on meat consumption are often dissimilar between countries (Chamhuri & Batt, 2013). For example, U.S. (Stampa, Schipmann‐Schwarze, & Hamm, 2020) and Swiss people's (Aepli & Finger, 2013) concerns are more on people's attitude and meat price, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, U.S. (Stampa, Schipmann‐Schwarze, & Hamm, 2020) and Swiss people's (Aepli & Finger, 2013) concerns are more on people's attitude and meat price, respectively. In Malaysia, the poor eating quality of meat is one of the significant factors apart from halal certification that contribute to this reduction (Mohd, Basri, Kamarulzaman, & Shamsudin, 2018; Basri, Nawi, Kamarulzaman, & Shamsudin, 2017; Chamhuri & Batt, 2013; Tey, Mad Nasir, Zainalabidin, Amin, & Radam, 2010). Quality beef should consistently satisfy customer expectations for eating and cooking method.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the consumers' WTP in two different market channels shows that consumers consider their WTP for a certain attribute for better quality based on the value for money (Chamhuri and Batt, 2013c). In the modern channel, consumers had a higher WTP for government certification, compared to the WTP for other poultry meat attributes.…”
Section: Discussionmentioning
confidence: 99%
“…The consumers' preferences and WTP for meat attributes have been an ongoing focus in many consumer studies (Font-i-Furnols and Guerrero, 2014;Grunert et al, 2004;Kehagia et al, 2007). Studies on meat quality attributes indicated several intrinsic (color, fat content, marbling) and extrinsic (price, origin, quality labels) cues as the most important factors in the consumers' intention to purchase food (Chamhuri and Batt, 2013c;Font-i-Furnols and Guerrero, 2014;Grunert, 2005;Grunert et al, 2004;Henchion et al, 2014;Hoffmann, 2000;Kennedy et al, 2004;Verbeke and Viaene, 1999). Some studies examined these cues as quality attributes for poultry meat (Castellini et al, 2008;Fletcher, 2002;Samant and Seo, 2016;Verbeke and Viaene, 1999).…”
Section: Selection Of Poultry Meat Attributes and Consumers' Wtpmentioning
confidence: 99%